L’effet de stimuli externes et des variables individuelles sur le traitement initial de l’information par le consommateur - Dufour, Jean-Claude; Martel, Jean-Marc (L'Actualité économique)

(untitled) (HEC Montréal, 1982)
AbstractThe neo-classical economic theory of the consumer behavior defines a utility function in terms of a global number of characteristics a product process or the result of several purchase activities. Every consumer can be in the context of aninefficient consumption function if the choice of the product bought doesn't fit with the state of preferences for the characteristics of this product. Thus, an efficient consumption function requires an adequate level of information that the mechanics of the market performance doesn't guarantee as well as for the consumption function as for the production function.In this paper, the consumer information processing limit is exposed showing an important gap between the preferred and memorized information by the consumer during the decision process. The concept of pre-processed information proposed could possibly improve the efficiency of the consumption function.